(3bUI GdebOGO Hf GdCShO GdcfOi hZRhGJg heGLQi dg eY GHfI Yeg GdejGSIs
(3ChdgG (B:s
(3HSe Gddg Gdedc GdY`dGe ai jJOC fXei hai cdGei s
(3BNQgG (B:s
(3hJNJe HGdUdGI hGdJMjI Ydi NjQ GdYhGde hGdHQjI s
(3PcQ HQhcdeGf fSNI CNQi ef gPG GdcJGH hCf eDdagG gh GdMLjL GdefjQ GdMQjQi GdeJhai SfI (B1256(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B235 s
(3eUOQ GbJfGA GdCUd (B:s
(3JhHLf HCdeGfjG (B(4355/ 715) s
Keywords: (3GdJGQjNs